An Examination of Student Preferences and Career Aspirations in Kotawaringin - Central Kalimantan : Implications for Vocational Education - Mairing, Jackson Pasini; Wiyogo, Wiyogo; Husnatarina, Fitria; Widiastuti, Lusia; Supriyadi, Supriyadi (Journal of Vocational Education Studies, 2025)
This study underscores the urgent need for vocational education in Kotawaringin, Central Kalimantan, to meet industry demands and public expectations for accessible and high-quality education. The findings indicate a strong interest in vocational training aligned with local industries, with the majority of respondents (67.79% male) recognizing its role in workforce preparedness. Most 11th-grade students (46.21%) prefer entering the workforce immediately after graduation (61.05%), particularly in the mining sector (30.06%), due to financial constraints and concerns regarding university graduates' employment prospects. The majority of respondents come from SMKN 2 Sampit (37.94%) and SMKN 1 Pangkalan Lada (36.09%). Bridging the gap between career preferences and labor market needs requires awareness campaigns, scholarships, internships, and industry partnerships. Key strategies include strengthening school-industry collaboration, enhancing infrastructure, developing competency certification programs, improving teacher training, promoting curriculum flexibility, and expanding financial aid. Broadening financial assistance is crucial for accessibility. These measures are expected to equip graduates with relevant skills, foster regional economic growth, and strengthen the sustainability of the workforce.